2021
DOI: 10.1186/s13045-021-01040-2
|View full text |Cite
|
Sign up to set email alerts
|

FGFR-TKI resistance in cancer: current status and perspectives

Abstract: Fibroblast growth factor receptors (FGFRs) play key roles in promoting the proliferation, differentiation, and migration of cancer cell. Inactivation of FGFRs by tyrosine kinase inhibitors (TKI) has achieved great success in tumor-targeted therapy. However, resistance to FGFR-TKI has become a concern. Here, we review the mechanisms of FGFR-TKI resistance in cancer, including gatekeeper mutations, alternative signaling pathway activation, lysosome-mediated TKI sequestration, and gene fusion. In addition, we sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 128 publications
(177 reference statements)
2
71
0
Order By: Relevance
“…Deregulated metabolism can drive further mutations (e.g., gatekeeper mutations in kinase domain of FGFR) leading to cross-resistance and thus to the ineffectiveness of even the most specialized strategies [ 195 , 196 , 226 , 227 , 228 ]. On the other hand, reports of positive effects of FGF/FGFR on chemotherapy further emphasize the complexity of the whole system [ 246 , 247 , 248 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Deregulated metabolism can drive further mutations (e.g., gatekeeper mutations in kinase domain of FGFR) leading to cross-resistance and thus to the ineffectiveness of even the most specialized strategies [ 195 , 196 , 226 , 227 , 228 ]. On the other hand, reports of positive effects of FGF/FGFR on chemotherapy further emphasize the complexity of the whole system [ 246 , 247 , 248 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, tremendous progress has been made in modulating or correcting aberrant FGF/FGFR signaling [ 12 , 105 , 194 , 195 ]. Such a strategy includes the application of receptor inhibitors, ligand traps, monoclonal antibodies, microRNAs, and combination therapy ( Figure 4 ) [ 12 , 105 , 194 , 195 , 196 ].…”
Section: Sensitization Of Tumor Cells To Chemotherapy By Inhibition Of Fgf/fgfr Complex Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Inhibition of cancer-promoting kinases has been considered to be an established therapeutic strategy for treating many cancer types ( 52 ). In our previous study, FGFR tyrosine kinase inhibitors (TKIs) were shown to repress the proliferation, differentiation, and migration of cancer cells, showing that they have great potential for development in precision medicine and individualized treatment of cancer patients ( 53 ). Therefore, further research on the development of post-translational modifications and, in particular, kinase inhibitors targeting the MCM complex would be beneficial for cancer treatment.…”
Section: Discussionmentioning
confidence: 99%